"Translated and adaptation into Persian of the podiatric health questionnaire (PHQ)". Issue 2 (May 2023) - Ahmadnezhad, Leila; López-López, Daniel; Becerro-de-Bengoa-Vallejo, Ricardo; Jiménez-Cebrián, Ana María; Gómez-Salgado, Juan; Losa-Iglesias, Marta Elena; Andreo-García, Maria Victoria; Navarro-Flores, Emmanuel
Abstract: The Podiatric Health Questionnaire (PHQ) is a foot health psicometric tool consisting of six items for measuring foot health status. Currently, PHQ has been adapted into Spanish. Thus, this research focused on develop the Persian translation and adaptation of the PHQ. The translation into Persian and test-retest reliability methods were applied from english version questionnarie. As regards to the total mark for each sub-scale, internal consistency and reliability were determined by the Cronbach α and intraclass correlation coefficient (ICC) with a confidence interval (CI) of 95%. High internal consistency was shown for the six sub-scales: a) walk with a Cronbach α of 0.775; b) hygiene and c) nail care with 0.789 and 0.796 respectively; d) foot on pain with 0.779; e) concern domain with 0.788; and f) quality of life with 0.798; and g) visual analogic scale with 0.803. Excellent test-retest reliability (ICC = 0.912 [95% CI = 0.845–0.950]) was shown for the total score. Conclusions: The persian version of the PHQ was shown to be a valid and reliable tool for an acceptable use in the Iran population. Highlights: We carry out test-retest reliability and the cross-cultural adaptation for the Persian Podiatric Health Questionnaire version (PHQ - P). PHQ - P was displayed as a accurate and reliable instrument with an adequate management in the Persian people. This tool record global or each domain values for evaluate foot health status.